Desempenho dos programas de p??s-gradua????o stricto sensu em administra????o, ci??ncias cont??beis e turismo no Brasil: um estudo dos programas no per??odo de 2001 a 2009 - Martins, Cibele Barsalini (2013)
In this research, it was analyzed how the evaluation system of Higher Education Personnel Improvement Coordination CAPES did influence the Brazilian stricto sensu post-graduate programs of Administration, Accounting Sciences and Tourism areas to adopt strategies and allocate their resources in the pursuit of development and improvement programs. The research was theoretically supported by the studies related to evaluation system, such as Maccari (2008) and the strategies studies, more specifically about the Resource-Based View RBV, initiated by Penrose (1959). As methodological characteristics, the study was descriptive, documentary, exploratory and qualitative. As results, it was verified that excellency quality programs, recognized national and internationally, presented deliberate strategies (MINTZBERG, 1978) systematically over the years, focusing on the improvement of their performance in the evaluation system of CAPES. By consequence, it brought structure improvements and resources availability, so that the programs could provide their researchers, the ability to focusing exclusively on their researches. Furthermore, it was possible to verify three effects of the strategies adopted by the programs: a) the frequency and the number of masters and doctors titled each year; b) the dynamism in the composition (changes/adjustments) of teaching staff; c) consolidation of the network co-authorship publications among faculty teachers within the program. It was found that programs progressed consecutively between the years 2001 to 2009 and got six and seven notes in the triennium 2007-2009, had the principle in their decision-making, which includes the choice of strategy to be adopted, the criteria of evaluation system of CAPES.